Circular Microstrip Patch Array Antenna for C-Band Altimeter System - Asghar Keshtkar; Ahmad Keshtkar; A. R. Dastkhosh (International Journal of Antennas and Propagation)
The purpose of this paper is to discuss the practical and experimental results obtained from the design, construction, and test of an array of circular microstrip elements. The aim of this antenna construction was to obtain a gain of 12 dB, an acceptable pattern, and a reasonable value of SWR for altimeter system application. In this paper, the cavity model was applied to analyze the patch and a proper combination of ordinary formulas; HPHFSS software and Microwave Office software were used. The array includes four circular elements with equal sizes and equal spacing and was planed on a substrate. The method of analysis, design, and development of this antenna array is explained completely here. The antenna is simulated and is completely analyzed by commercial HPHFSS software. Microwave Office 2006 software has been used to initially simulate and find the optimum design and results. Comparison between practical results and the results obtained from the simulation shows that we reached our goals by a great degree of validity.